The Effect Of Video Education On Social Stigma in People With Mental Disorders in Tinalan Village Kediri City - Kurnia Sari, Dhita; Yunita Frida Haubenu; Reni Nurhidayah (Universitas STRADA Indonesia, 2024)
Mental health was still a significant health problem in the world, included in Indonesia. This negative label as a crazy person is unconsciously a self-created stigma, so the impact was that families or the community around people with mental disorders don't want to take care of it so that if allowed to continue, the rights of people with mental disorders will be neglected, for example social rights and the right to treatment. The purpose of this study was to determine the effect of video education on social stigma in people with mental disorders. The research design was a one group pre-test-posttest pre-experimental design. The independent variable is video education while the dependent variable is society's stigma towards people with mental disorders. The population is the entire community in RT: 01 RW: 13 in Kediri Tinalan Village, Kediri City, a sample of 43 respondents using a purposive sampling technique. Data collection techniques using a questionnaire.The results showed that before being given treatment, most respondents (65.1%) had a high stigma towards people with mental disorders, namely 28 respondents and after being given treatment, almost all respondents (93.0%) had a low stigma. Data analysis used the Wilcoxon test with sig value (2-tailed) or pvalue = 0.000 and error rate or = 0.05, so p <, 0.000 <0.05 so H1 is accepted, meaning that there is an effect of video education on social stigma in people with mental disorders souls in the Tinalan Village, Kediri City. It is hoped that the community can add insight and information about stigma on ODGJ so that they can show good attitudes and behavior towards ODGJ.